1975
DOI: 10.1530/acta.0.0800014
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Insulin and Somatomedin a to Human Placental Membrane

Abstract: A particulate membrane fraction from human placental membrane was shown to be rich in binding sites not only for insulin but also for somatomedin A. The binding of the 125I-labelled peptide was time and temperature dependent. Degrading activity present in the membrane fraction was negligible at +4\s=deg\C. The Scatchard plot for insulin binding revealed two types of binding sites with an apparent high affinity constant of 3.8\m=x\ 108 m\ m=-\ 1 and with 5.4 \ m=x\10\m=-\9 moles of binding sites per mg of membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 17 publications
4
40
0
Order By: Relevance
“…The placenta contains receptors for several peptide hormones including insulin [23], epidermal growth factor [24], the somatomedins [25][26][27] and gonadotrophin releasing hormone [28] and has been used as a source of receptor for the purification of several of these. In this study we have identified, and characterized, CT receptors in a human placental membrane fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta contains receptors for several peptide hormones including insulin [23], epidermal growth factor [24], the somatomedins [25][26][27] and gonadotrophin releasing hormone [28] and has been used as a source of receptor for the purification of several of these. In this study we have identified, and characterized, CT receptors in a human placental membrane fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The MSA receptor in hiunim placenta can be compared with the receptors for insulin (Posner, 1974), somatomedin A (Takano et al, 1975) and somatomedin C (D'Ercole et al, 1976) in this tissue. All have similar properties of time, temperature and pH dependence as well as reversibility of binding by lowering the pH.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in these particular hormones/factors as modulators of placental metabolism has been fuelled, in part, by the demonstration of specific, membrane-associated receptors in the human placenta (25,36,38,43,46,48,54,57), two of which (for insulin and EGF-URO) have been partially purified (26,28,60). Placental cytosolic binding proteins for some of the IGFs have also been described (7,22).…”
Section: Speculationmentioning
confidence: 99%